The effect of the thickness of indium oxide films on the spectral response of monocrystalline solar cells (Journal of the College of Basic Education, 2022)
This research deals with the effect of In2O3 films deposited on the surface of silicon solar cells p-n junction as an anti-reflection coating on the efficiency of the solar cell and the detection properties. nm), within different oxidation temperatures ranging from (350-400-450C°).The measurements of the short-circuit current and the open-circuit voltage showed a remarkable improvement in the conversion efficiency of the solar cell after coating it with In2O3 film, as it was (3.95%) before coating and became (10.95%) when a film was deposited with a thickness of 500 nm and an oxidation temperature of 450C°.